Differential Radial Capillary Action of Ligand Assay (DRaCALA). Issue 1 (3rd December 2018) - Seminara, Anna B.; Turdiev, Asan; Turdiev, Husan; Lee, Vincent T.
Abstract: Protein interactions with nucleic acids are important for the synthesis, regulation, and stability of macromolecules. While a number of assays are available for interrogating these interactions, the differential radial capillary action of ligand assay (DRaCALA) has been developed as an easy and flexible platform that allows for the study of individual interactions when carrying out high‐throughput screening for novel binding proteins and small molecule inhibitors. In this article, we describe the principle of DRaCALA and methods that utilize DRaCALA to determine the affinity and specificity of individual protein‐nucleic acid interactions as well as uses for screening for binding proteins and chemical inhibitors. © 2018 by John Wiley & Sons, Inc.